Pilot symbol assisted channel estimation for 4x4 space time block coded spatial modulation systems - Doğan, Hakan; Panayırcı, Erdal; ACAR, YUSUF (IEEE, 345 E 47th St, New York, Ny 10017 USA, 2015)
Recently, spatial modulation (SM) and space-time block coding (STBC) are combined to take advantage of the benefits of both while avoiding their drawbacks for multiple-input and multiple-output (MIMO) systems. The pioneering works on STBC-SM assume that perfect knowledge of the channel fading coefficients is available at the receiver. This work(1) addresses the challenging and timely problem of channel estimation for 4 x 4 STBC-SM systems in the presence of time-varying channels. In this paper, the estimation of channel at pilot durations is done by least square (LS) method and then the channel interpolation is performed by linear interpolation or nearest neighbor interpolation algorithms. Simulation results have demonstrated that the proposed channel estimation based on the linear interpolation offer substantial performance gains over the channel estimation based on the nearest neighbor interpolation. In particular, a savings of about 5dB is obtained at BER = 10(-5), as compared with the nearest interpolation based receiver at 120km/h for 4 x 4 STBC-SM systems with the binary phase shift keying (BPSK) modulation.
Keywords: Spatial Modulation; Space-Time Block Coding; Pilot Symbol Assisted Channel Estimation; Multiple-Input Multiple-Output; Time Varying Channels